Wayang Bèbèr Damarwulan - Mahmudi Mahmudi (Wayang Nusantara: Journal of Puppetry, 2018)
This “Wayang Bèbèr Damarwulan” work is an interpretation of wayang bèbèr based on the creator’s experience in studying arts. This work is a wayang Bèbèr artwork using traditional picture language (two dimension theory) and shape transformation theory. Both of these theories are used to combine the art of “kethoprak” with the story of Damarwulan into Wayang Bèbèr which then performed as a new version of wayang Bèbèr. By combining kethoprak into wayang Bèbèr, it is expected to be a new attractive and interesting wayang Bèbèr performance for the society. Karya Wayang Bèbèr Damarwulan adalah suatu bentuk interpretasi baru dari wayang bèbèr. Interpretasi baru ini lahir dari pengalaman yang diperoleh perancang selama menekuni dunia seni, baik seni lukis maupun seni pedalangan. Karya Wayang Bèbèr Damarwulan ini merupakan penggarapan wayang bèbèr berdasarkan teori bahasa rupa tradisional/RWD (teori ruang waktu datar) dan teori alih wahana. Kedua teori tersebut digunakan sebagai kerangka berpikir dalam merancang Wayang Bèbèr Damarwulan yang merupakan sebuah karya wayang bèbèr versi baru perpaduan antara kethoprak cerita Damarwulan dengan wayang bèbèr. Karya ini diharapkan dapat membuat pertunjukan wayang bèbèr semakin menarik dan diminati masyarakat.